DECODING THE BEST PROGRAMMING LANGUAGE FOR WATERFALL-STYLE WEBSITE BACKEND DEVELOPMENT - Santoso , P. B.; Reynaldi, D. T. (Advanced Journal of Environmental Sciences (AJES), 2022)
Programming languages serve as the bridge between humans and machines, enabling the creation of various applications, websites, and games. This journal focuses specifically on programming languages used for websites, which are applications containing documents, photos, images, videos, and music accessible through the HTTP protocol via a web browser. Websites have diverse functions, including serving as learning platforms, promotional tools, and platforms for e-commerce activities. Typically, websites are built using HTML, CSS, and JavaScript. HTML, or Hypertext Markup Language, describes the structure of a website. CSS (Cascading Style Sheets), while not a programming language, enhances the visual aesthetics of websites. JavaScript, on the other hand, is a versatile programming language that allows for both frontend and backend development. To create dynamic websites, additional backend technologies are required. Common choices include PHP, Python, Java, and C#. PHP, originally standing for Personal Home Page, is a language similar to Java, C, and Perl. Java, developed by Sun Microsystems, is a widely-used language known for its application in both backend and Android development. Python, a multipurpose interpreted language, boasts clear syntax and is extensively used in data science and artificial intelligence. C#, developed by Microsoft, offers productivity, flexibility, and convenience compared to previous applications like Visual Basic. This journal explores the features, advantages, and applications of programming languages for website development, shedding light on their diverse capabilities. By understanding the strengths and purposes of these languages, developers can make informed choices when building websites and ensure efficient and effective outcomes.